1968
DOI: 10.1128/jvi.2.10.1038-1046.1968
|View full text |Cite
|
Sign up to set email alerts
|

Replication of Western Equine Encephalomyelitis Virus II. Cytoplasmic Structure Involved in the Synthesis and Development of the Virions

Abstract: Analysis of the cytoplasmic fraction of chick embryo cells during the exponential phase of Western equine encephalomyelitis (WEE) virus growth showed that the viral ribonucleic acid (RNA) labeled by a short pulse with 3 H-uridine was associated with a structure which sedimented in sucrose density gradients with a coefficient of 65 S . The RNA extracted from this structure sedimented in sucrose density gradients at 26 S . After a longer per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
15
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 12 publications
5
15
0
Order By: Relevance
“…Most of the 3H-RNA remained associated with some 14C protein in a particle with a sedimentation coefficient of 120S, whereas most of the "4C-protein was released to appear near the top of the gradient in a peak at 10 to 20S. Thus, deoxycholate treatment appears to split the virion producing an RNAprotein "core" particle and protein "envelope" material of much lower S value, in similar fashion to that observed with group A arboviruses (13,16). A small amount of free viral RNA appeared to have been released also, sedimenting slightly faster than the envelope protein.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…Most of the 3H-RNA remained associated with some 14C protein in a particle with a sedimentation coefficient of 120S, whereas most of the "4C-protein was released to appear near the top of the gradient in a peak at 10 to 20S. Thus, deoxycholate treatment appears to split the virion producing an RNAprotein "core" particle and protein "envelope" material of much lower S value, in similar fashion to that observed with group A arboviruses (13,16). A small amount of free viral RNA appeared to have been released also, sedimenting slightly faster than the envelope protein.…”
Section: Methodssupporting
confidence: 54%
“…Characterization of group A arbovirus proteins by polyacrylamide gel electrophoresis indicates that there are only two, possibly three, structural proteins in the virion and from 5 (with Semliki Forest virus) to 14 (with Sindbis virus) proteins induced in the cytoplasm of infected cells (2,6,7,13,15,16,21). Group B arboviruses are smaller and comprise a larger, more complex group of viruses (1,3).…”
mentioning
confidence: 99%
“…The RNA within nucleocapsids of two other group A arboviruses, Westem equine encephalitis virus (16) and Sindbis virus (4,17), has also been reported to be digested by ribonuclease treatment. Sensitivity of the RNA within Semliki Forest virus ntucleocapsids to digestion by ribonuclease.…”
mentioning
confidence: 99%
“…It has been reported that there is a 130-140 S structure containing 40-45 S virion RNA in cells infected with group A arboviruses [2,5,8,27] including Chikungunya virus [15]. This structure corresponds to nucleocapsid (NC) of the virion in respect to its protein subunit [6,17,27], ability to yield infective RNA [5,15], morphology [8,16], and its role as a precursor of the virion as determined in pulse-chase experiments [14,27]. Besides NC, there exists a 65 S component which contained single-stranded 26 S virus-specific RNA [2,5,8,27].…”
mentioning
confidence: 99%
“…This structure corresponds to nucleocapsid (NC) of the virion in respect to its protein subunit [6,17,27], ability to yield infective RNA [5,15], morphology [8,16], and its role as a precursor of the virion as determined in pulse-chase experiments [14,27]. Besides NC, there exists a 65 S component which contained single-stranded 26 S virus-specific RNA [2,5,8,27]. These were suspected to be precursors of NC and virion RNA, respectively [4,5,10].…”
mentioning
confidence: 99%